Pengaruh Penerapan Standar Pelaporan Akuntansi Sektor Publik Dan Pengawasan Keuangan Daerah Terhadap Akuntabilitas Kinerja Instansi Pemerintah Pada Dinas Pekerjaan Umum Kota Makassar - Lusiana Kanji (Insan Cita Bongaya Research Journal, 2024)
This study aims to determine the Application of Public Sector Accounting Reporting Standards and Regional Financial Oversight of Performance Accountability of Government Agencies at the Makassar City Public Works Service. Data collection uses primary data obtained from questionnaires using the Slovin formula. The population is all employees of the Makassar City Public Works Office, while the sample taken is 83 respondents. The results of the questionnaire have been tested for validity and reliability, and classical assumptions have been tested in the form of normality assumptions and heteroscedasticity assumptions. Methods of data analysis using multiple regression techniques. The results of the study show that the application of Public Sector Accounting Reporting Standards and Regional Financial Supervision has a positive and significant effect on Government Agencies Performance Accountability.